MiRNA: local guardians of presynaptic function in plasticity and disease. Issue 7 (3rd July 2021) - Woods, Brandon J.; Van Vactor, David
ABSTRACT: Environmental fitness is an essential component of animal survival. Fitness is achieved through responsive physiological plasticity of tissues across the entire body, and particularly in the nervous system. At the molecular level, neural plasticity is mediated via gene-environmental interactions whereby developmental cues and experience dependent input adapt neuronal function to ever changing demands. To this end, neuronal gene regulation must be coupled to changes in neural activity. Seminal discoveries of the 20th century demonstrated neural activity modifies gene expression through calcium-dependent gene transcription. Building on this model, recent work over the last two decades shows that mRNA products of transcriptional programming continue to be regulated in the neuron through the activity-dependent post-transcriptional action of microRNAs (miRNAs). miRNAs are special post-transcriptional regulators that can tune gene expression within the spatial and temporal requirements of synaptic compartments. This mode of gene regulation has proven to be essential for synaptic function and plasticity as miRNA loss of function is highly associated with neural disease. In this review we will discuss current perspective on the link between presynaptic plasticity and miRNA biogenesis in the neuron.